Reading the political in Jewish and Christian texts - Snyder, Julia A., 1980-; Zamfir, Korinna; Healey, Spencer (Biblical tools and studies., 2020)
"Anti-imperial" readings of ancient texts are popular, but are they right? What does it mean to engage in "political" interpretation of ancient texts? What can Biblical scholars learn from Classicists about the emperor cult? These are a few of the questions addressed in this volume. Highlighting the work of scholars in Eastern and Western Europe, it offers fresh perspectives on "political" aspects of early Jewish and Christian texts. Contributions include exegetical studies with literary and historical interests, as well as critical hermeneutical reflection. Essays analyze texts from the Hebrew Bible, Septuagint, and New Testament, plus Josephus and extra-canonical Christian literature